Empowerment As a Trojan Horse: New Systems of Work Organization in the North American Automobile Industry - Yates, Charlotte A. B. (Charlotte Alyce Bronwen); Lewchuk, Wayne; Stewart, Paul (Economic and Industrial Democracy, 2001)
While new models of work organization (lean production) in the automobile industry have been portrayed as a 'democratic' break with Fordism, we find considerable parallels with those traditional patterns of labour control they were intended to supplant. Far from understanding these as exemplars of 'democratic Taylorism', the article identifies specific company responses to problems associated with declining productivity and competitiveness. Moreover, the article argues that new models of work organization associated with lean production, far from heralding empowerment, are more conerned with asserting management control in varying ways in different companies.